Transfeminism and Political Forms of Life - Martha Alicia Trevino-Tarango (Nordic Wittgenstein Review, 2022)
It is sometimes argued that there are pre-political, ‘natural’ characteristics that have a significant role in rendering political subjects, for instance that women are the subjects of feminism. These same arguments criticise transfeminism as a usurper of feminist priorities because it changes focus to the rights of groups whose members are not exclusively women. This essay challenges such criticism. It begins by defining transfeminism as a form of activism and an epistemological tool, in order to cogently address some of the views that oppose it. I then propose a way out of the conflict by showing how we can make better sense of transfeminism aided by Wittgenstein’s concept of forms of life, since both views contend that there are biological and environmental features that constitute the uniqueness as well as the diversity of the given human form of life, without implying that said diversity leads to relativism. The paper concludes that transfeminism, when conceptualised correctly, can indeed work with other feminisms and political movements in order to counter institutionalised and market-driven gender politics that only simulate to address feminist concerns.